Reliability and validity of the turkish version of the family caregiver medication administration hassles scale - SANCAR, MESUT; AY, NADİYE PINAR; OKUYAN, BETÜL (My University, 2023)
Background: The Family Caregiver Medication Administration Hassles Scale (FCMAHS) was developed to evaluate the hassles and concerns experienced by family caregivers in medication administration.Objective: This study aimed to evaluate the reliability and validity of the Turkish version of the Family Caregiver Medication Administration Hassles Scale (FCMAHS-TR).Methods: The FCMAHS-TR was developed after translation, cultural adaptation, and a pilot study. The cross-sectional study was conducted among family caregivers (=18 years) in community pharmacies. Test-retest reliability analysis, exploratory factor analysis (EFA), and confirmatory factor analysis (CFA) were performed. Hypothesis testing was used for the assessment of construct validity.Results: The majority (68.7%) of the family caregivers were female (n = 470). In the test-retest reliability analysis (n = 30), the ICC value was 0.917 (P < 0.001). In EFA analysis (n = 251), the Kaiser-Meyer-Olkin (KMO) measure was 0.799, 62.6% of the total variance was explained by five factors including eighteen items, and Cronbach\"s alpha was 0.836. According to CFA (n = 219), the root mean square error of approxi-mation (RMSEA) was 0.0654, and the comparative fit index (CFI) was 0.918. In construct validity, family caregivers with low reading ability of health-related materials and with high care burden had significantly higher median scores for all the factors of the FCMAHS-TR (P < 0.05 for all).Conclusions: The FCMAHS-TR can be used to evaluate the hassle and concerns experienced by family caregivers in medication administration. This scale can be used by healthcare professionals to identify family caregivers who need individualized interventions for medication adminis-tration hassles.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; BİRİNCİL SAĞLIK BAKIMI; Klinik Tıp; Klinik Tıp (MED); TIP, GENEL & DAHİLİ; PRIMARY HEALTH CARE; CLINICAL MEDICINE; Clinical Medicine (MED); MEDICINE, GENERAL & INTERNAL; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; care burden; family caregiver; hassles; health literacy; medication administration; validation; INFORMAL CAREGIVERS; HEALTH LITERACY; OLDER-ADULTS; MANAGEMENT; PEOPLE; OUTCOMES; ASSIST